Saúde da família e educação médica: reflexões a partir da experiência de um curso de medicina no sertão paraibano - Medeiros, Henrique Gonçalves Dantas de (2016)
Taking under consideration the medical education reform processes in recent years and the current debate on the transference of medicine undergraduate courses to the countryside, the need of studying the experiences that have arisen after the 2001 National Curriculum Guidelines is visible. As a result, it was sought to analyze the experience UFCG medicine school located in Cajazeiras, moreover, report the history of the course; evaluate the present challenges; consider the theoretical foundations of the Pedagogical Project of the Course (PPC); describe the insertion of Public Health / Family Medicine in the curriculum; consider whether this PPC meets the requirements of Primary Health Care; describe how the aspects related to the world of work, pedagogical project, pedagogical approach, practice scenarios and teacher development are experienced; recognize contradictions between PPC and real conduction; and excerpt generalizations that may support public policies. This research is based on Marxist frame of reference. Historical, monographic and comparative methods of procedure were used. It has a qualitative approach. Its characteristics are descriptive and exploratory. Indirect documentation (documentary and bibliographic research) and Intensive Direct Observation - participant observation, which, in the beginning was unsystematic and later systematic, following the instrument developed by Lampert, were adopted as data collection techniques. As data analysis technique, the hermeneutic-dialectic method. The story of the course reveals the tension between low absorptive capacity of the local health system and institutional characteristics of UFCG (teaching staff, PPC). The first aspect was the main pole of the contradiction in the early years, which was partially overcome thanks to the reduction of annual entries, possibility of supervised internships in other institutions and UFCG‟s own hospital services establishment. Only then, the Teacher Development gained preeminence among the present challenges. Starting from common problems of Rural Medicine, PPC has a great eclecticism: it flirts with the Historical and Dialectical Materialism by Latin American Critical Epidemiology, which bases its understanding of medicine, and Methodology of Problematization, with the understanding of the student as a subject and diversification of learning spaces; referencing on Skills Pedagogy, conforms to currents of rationalist imprint, individualistic and neopragmatist nature; and, finally, the Postmodernism of Contestation, of Boaventura de Sousa Santos, and the Complex Thought, of Edgar Morin, establish an ethical understanding of the human being and Science, which guides assumptions of curricula based on humanism and research as a conductor axis of teaching. The course is aligned with the guidelines of ABEM / SBMFC for teaching in primary health care, which is inserted since the first year, by teaching of collective approaches of the health-disease process. Training in primary health care emphatically continues in the fourth term when community and family approaches in the territory are studied, developing Residency in Family Medicine and where, during the intermediate following years and the supervised internships, individual clinical approach in Primary Health Care is trained. Throughout the path, different methodologies are worked such as living in communities, tutorial groups for follow Singular Therapeutic Projects, seminars, etc. The course presents Innovative with Advanced Trend profile, and Teaching Development is a critical point, revealing their fundamental contradiction: the advancements in theory are not fully expressed in practice. It is both concluded that the medical educational policies of transference of the undergraduate course to the countryside should prioritize the analysis of the health network, and that changes in medical education depends on political action, presenting an agenda of proposals.